Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.jgr.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Panax ginseng and its ginsenosides: potential candidates for the prevention and treatment of chemotherapy-induced side effects

Abstract: Chemotherapy-induced side effects affect the quality of life and efficacy of treatment of cancer patients. Current approaches for treating the side effects of chemotherapy are poorly effective and may cause numerous harmful side effects. Therefore, developing new and effective drugs derived from natural non-toxic compounds for the treatment of chemotherapy-induced side effects is necessary. Experiments in vivo and in vitro indicate that Panax ginseng ( PG ) and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 85 publications
(106 reference statements)
0
43
0
Order By: Relevance
“…An experimental study demonstrated that P. ginseng mitigated the electrocardiographic and histopathological changes induced by DOX and restored the antioxidant capacity ( Chen et al, 2021 ). Another study reported that P. ginseng constituents might be a novel candidate for improving DOX-induced cardiotoxicity ( Wan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An experimental study demonstrated that P. ginseng mitigated the electrocardiographic and histopathological changes induced by DOX and restored the antioxidant capacity ( Chen et al, 2021 ). Another study reported that P. ginseng constituents might be a novel candidate for improving DOX-induced cardiotoxicity ( Wan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Febuxostat is a xanthine oxidase inhibitor indicated in patients with gout suffering from hyperuricemia, and it is used chiefly in the management of chronic gout (Zhang et al, 2021). With minimal adverse effects, Febuxostat is more effective than allopurinol at its standard doses ( Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenosides are the main active components of ginseng [ 7 ], which is a rare and precious Chinese medicine produced in Northeast China. Traditional Chinese medicine is famous for its multiple pharmacological effects and mild side effects [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…CYC is associated with cardiomyocyte apoptosis, inflammation, endothelial dysfunction, calcium dysregulation, endoplasmic reticulum damage, and mitochondrial damage [ 24 ]. Several molecular mechanisms were proposed discussing CYC induced cardiotoxicity, e.g., through Nrf2/HO-1 [ 25 , 26 ], PI3K/Akt/mTOR [ 25 , 26 ], SIRT1/FoxO1 [ 27 ], Akt/GSK-3β/NFAT/calcineurin [ 22 ], p53/p38MAPK [ 26 ], and TLR4/NFκB [ 19 , 28 ], among other signaling pathways. CYC undergoes hepatic metabolism to produce of aldophosphamide, which further decomposes into phosphoramide mustard, the active neoplastic metabolite, and acrolein, the detrimental metabolite [ 29 ].…”
Section: Introductionmentioning
confidence: 99%